The Peculiarities of Simulating the Process of Selecting an Optimal Solution for the Diversification of Agricultural Production - KUSSAIYNOV, Talgat; SHAIKENOVA, Nurgul; BULASHEVA, Ainur (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
Recommendations for the diversification of crop production could be of practical value only when they take into account not only natural and economic factors but also economic risk factors and manufacturers’ attitude to risk. The selection of the diversification strategy in the sector is largely determined by the degree of risk aversion on the part of entrepreneurs. The use of crop production mathematical risk models makes it possible to select the most preferable ways of diversification under contemporary market conditions.